1982
DOI: 10.1002/1097-0142(19821215)50:12<2884::aid-cncr2820501231>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Predicting breast cancer recurrence

Abstract: The prognostic value of 435 cytochemical, cytometrical, morphological, epidemiological, and clinical variables was analyzed in a prospective study of 179 breast cancer patients followed for five years after mastectomy. A variable reduction was obtained by first selecting variables correlated with recurrence rate in direct (Student's t test) or correlation analysis with consideration of the type of variable analyzed (nominal, interval, ordinal). The 20 variables most strongly correlated with recurrence were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…[4][5][6][7] Patients with breast cancer treated with digitalis have been found to have a lower death rate compared with those not treated with digitalis. [4][5][6][7] Five years after mastectomy the cancer recurrence rate in controls not given digitalis was 9.6-fold that of patients treated with digitalis. [4][5][6][7] Recently, digitalis and other cardiac glycosides in nontoxic concentrations have been shown to induce apoptosis in different malignant cell lines in vitro.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…[4][5][6][7] Patients with breast cancer treated with digitalis have been found to have a lower death rate compared with those not treated with digitalis. [4][5][6][7] Five years after mastectomy the cancer recurrence rate in controls not given digitalis was 9.6-fold that of patients treated with digitalis. [4][5][6][7] Recently, digitalis and other cardiac glycosides in nontoxic concentrations have been shown to induce apoptosis in different malignant cell lines in vitro.…”
supporting
confidence: 88%
“…[1][2][3] Epidemiological studies have shown that digitalis has anti-cancer effects. [4][5][6][7] Patients with breast cancer treated with digitalis have been found to have a lower death rate compared with those not treated with digitalis. [4][5][6][7] Five years after mastectomy the cancer recurrence rate in controls not given digitalis was 9.6-fold that of patients treated with digitalis.…”
mentioning
confidence: 99%
“…A review of earlier work (Underwood, 1974) reported that in 8 studies, five showed a correlation between cell infiltration and 'good' prognosis, whereas three were negative. Since that time there have been numerojis additional conflicting rerports of associations between infiltration and for example favourable prognosis (Black et al, 1975;Dawson et al, 1982;Stenkvist et al, 1982), and poor prognosis (Roses et al, 1982;Fisher et al, 1983). However, a consistent theme in more recent studies has been the association of lymphoplasmacytic infiltration and histological features of poor prognosis such as poor grade, nuclear pleomorphism, tumour necrosis and lymph node invasion by tumour (Black et al, 1975;Lauder et al, 1977;Fisher et al, 1983;von Kleist et al, 1987;Zuk & Walker, 1987 Schoorl et al, 1976;Hsu et al, 1981;Hurlimann & Soraga, 1985;Lwin et al, 1985;von Kleist et al, 1987;Zuk & Walker, 1987 (1985) report that B cells can represent up to 48% of the total number of T cells, whilst Zuk and Walker (1987) provide evidence that the proportion of B cells increase relative to T cells in carcinoma as opposed to benign breast, with an overall B:T cell ratio as high as 1:2.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular significance are studies that indicate the beneficial effects of CTS therapy in women with breast cancer (25)(26)(27)(28)(29). Consistently, recent in vitro and in vivo studies have identified several new CTS compounds that exhibit anti-cancer activities (30 -32).…”
mentioning
confidence: 99%